Influence of total pressure on the microstructures and growth mechanism of ZrC coatings prepared by chemical vapor deposition from the Zr-Br2-C3H6-H2-Ar system. Issue 4 (March 2017) - Ma, Xin; Chen, Si'an; Mei, Min; Li, Yong; Hu, Haifeng; He, Xinbo; Li, Guangde; Qu, Xuanhui
Abstract: Zirconium carbide (ZrC) coatings were deposited on graphite substrates by chemical vapor deposition from the Zr-Br2 -C3 H6 -H2 -Ar system. The influence of total pressure on the growth of ZrC was investigated in the range of 5–60 kPa. As the total pressure increased, the deposition rate increased evidently, and the preferential orientation of ZrC coatings changed from the (200) plane to the (220) plane. The growth mechanism changed from a mass transport reaction to a surface reaction at the total pressure of 20–40 kPa. At the total pressure below 20 kPa, the deposition was dominated by crystal growth, so the coatings were composed of well-faceted pyramidal-shaped crystals growing along the <001> direction. At the total pressure above 60 kPa, the growth of ZrC coatings was controlled by the nucleation mechanism, so the coatings were cluster-like crystals rapidly growing along the <110> direction. In addition, low pressure was conducive to the formation of near-stoichiometric ZrC without free carbon. These variations of ZrC coatings can mainly be attributed to gas supersaturation and remarkably changed transport diffusion coefficients with increasing total pressure.